The sense of loneliness and meaning in life in post-COVID convalescents—a preliminary study - Sipowicz, Kasper; Pietras, Tadeusz; Mosiołek, Anna; Sobstyl, Michał; Ring, Michał; Kamecki, Krystian; Stefańczyk, Ignacy; Kosmalski, Marcin (Frontiers in Psychiatry, 2023)
Introduction: The COVID-19 epidemic has provided opportunity to study the impact of a well-defined severe illness on the development of a depressive episode and the associated sense of loneliness and lack of meaning in life. Material & Methods: The aim of the study was to assess the occurrence of a reactive depressive episode, the severity of depression, a sense of loneliness and meaning in life in subjects who approximately a year earlier than the date of the study had suffered from a pulmonary form of SARS-CoV-2 infection with radiologically documented interstitial lesions of the lungs, requiring and not requiring hospitalization compared to people who did not develop the disease as a result of infection with that virus. The study included 63 subjects hospitalized for pulmonary lesions, 67 not hospitalized and 60 healthy controls. The severity of depressive symptoms was measured using a Polish-language standardized version of the Beck Depression Inventory, a sense of loneliness using the De Jong Gierveld Loneliness Scale, and a sense of meaning in life using the Life Attitude Profile-Revised. Results: The frequency of depression and its severity were found to be the highest in hospitalized patients compared to those treated at home and healthy people. A significant difference in the frequency of depression and its severity between outpatients and healthy people was also observed. The feeling of loneliness turned out to be greatest in the group of hospitalized people. Also, the severity of loneliness was found to be higher in the outpatient compared to the control group. The sense of meaning in life reached its lowest level among hospitalized patients, was moderately reduced in the outpatient group, and typical of the Polish population in the control group. Discussion: Both pulmonary SARS-CoV-2 infection and hospitalization have been shown to be a risk factor for depression, increased feeling of loneliness and a reduced sense of meaning in life. The effect of trauma and the presence of depression can be the explanation for the increased sense of loneliness after the illness and the partial breakdown of the lifeline manifested by a decrease in the sense of meaning in life.